2015
DOI: 10.1039/c4ra16617e
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the binding properties of agonists interacting with human TGR5 using structural modeling, molecular docking and dynamics simulations

Abstract: TGR5, act as a potential pharmacological target in the treatment of type II diabetes. In the computational study, structural modeling and binding site prediction of TGR5 receptor was performed. Two well-known agonists of TGR5 used to investigate the mode and mechanism of binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…The Rg is an evaluating parameter for the behavior and stability of the biological systems during the MD trajectories by measuring the compactness of biomacromolecules’ structures [ 94 , 95 ]. The Rg can also be used as an indicator of whether the complex will maintain folded conformation after the MD simulation.…”
Section: Resultsmentioning
confidence: 99%
“…The Rg is an evaluating parameter for the behavior and stability of the biological systems during the MD trajectories by measuring the compactness of biomacromolecules’ structures [ 94 , 95 ]. The Rg can also be used as an indicator of whether the complex will maintain folded conformation after the MD simulation.…”
Section: Resultsmentioning
confidence: 99%
“…Homology models of TGR5 have been presented based on template structures of other seven transmembrane (7TM) domain receptors5678. We previously reported that the amino acids 285–294 at the TGR5 C-terminus form an alpha-helical stretch important for plasma membrane localization and thus responsiveness to extracellular ligands9.…”
mentioning
confidence: 99%
“…According to our previous theoretical study 20 , it was observed that the binding site of TGR5 was formed by active site residues including Ser21, Asn76, Tyr89, Asn93, Ser157, Trp237, Tyr240 and Ser270. Thus, the grid was generated at the centroid point of the active site for consistency.…”
Section: Grid Generation and Ligand Preparationmentioning
confidence: 97%